PENGARUH PENDIDIKAN, KOMPETENSI, PELATIHAN, DAN MOTIVASI TERHADAP MUTU PESERTA PELATIHAN PADA UPT BLK UKM KABUPATEN MUSI RAWAS - Ahmad Basri; Yohanes Susanto; Johan Kenedi (Jurnal Media Ekonomi (JURMEK), 2020)
This research was conducted with the aim to determine the Impact of education, competence, training and motivation on the quality of trainees partially and simultaneously. The research method used is a quantitative method, with data collection techniques using questionnaires and samples in this study amounting to 81 people consisting of training participants and organizing teams. Research Results The influence of education, competence, training and motivation on the quality of training participants at the UPT BLK UKM Musi Rawas. Obtained Fcount value of 212.522 and Ftable of 2.48. It means that there is a positive and significant influence of education, competence, training and motivation on the quality of training participants at the UPT BLK UKM Musi Rawas. The influence of education, training and motivation on the quality of the trainees in the UPT BLK UKM Musi Rawas Regency has a Fcount of 162.505 and a Ftable of 2.48. The Impact of competence, training and motivation on the quality of trainees in the UPT BLK UKM Musi Rawas Fcount value of 199.593 and Ftable 2.48 This shows that there is a positive and significant Impact of competence, training and motivation on the quality of trainees at the UPT BLK UKM Musi Rawas. The influence of education, competence and training on the quality of the trainees in the UPT BLK UKM Musi Rawas Regency has a Fcount of 162,505 and a Ftable of 2.48.